Cap-dependent RNA splicing in a HeLa nuclear extract. - Edery, I (1985)
We have studied the involvement of the 5' cap structure in the splicing of precursor mRNAs in a HeLa nuclear extract. We show that precursor mRNAs are spliced efficiently only when they possess a cap structure and that preincubation of a HeLa nuclear extract rendered the splicing reaction highly sensitive to inhibition by cap analogues. This sensitization was dependent on exogenous Mg2+ but not exogenous ATP or GTP. These results demonstrate that splicing in a nuclear extract is highly dependent on the cap structure, as was demonstrated for the splicing process in a HeLa whole-cell extract [Konarska, M. M., Padget, R. A. & Sharp, P. A. (1984) Cell 38, 731-736], and thus support the contention that cap recognition is an important feature of eukaryotic mRNA biogenesis.